Survey of Artificial Intelligence Approaches in Cognitive Radio Networks - Yasmina EL Morabit; Fatiha Mrabti; El Houssein Abarkan (Journal of Information and Communication Convergence Engineering, 17(1), 2019)
This paper presents a comprehensive survey of various artificial intelligence (AI) techniques implemented in cognitive radioengine to improve cognition capability in cognitive radio networks (CRNs). AI enables systems to solve problems by emulatinghuman biological processes such as learning, reasoning, decision making, self-adaptation, self-organization, and self-stability. The use of AI techniques is studied in applications related to the major tasks of cognitive radio including spectrum sensing,spectrum sharing, spectrum mobility, and decision making regarding dynamic spectrum access, resource allocation, parameteradaptation, and optimization problem. The aim is to provide a single source as a survey paper to help researchers betterunderstand the various implementations of AI approaches to different cognitive radio designs, as well as to refer interestedreaders to the recent AI research works done in CRNs. KCI Citation Count: 0